Sustained high pressure double balloon angioplasty of calcified conduits. Issue 2 (1st February 1999) - Sreeram, N; Hutter, P; Silove, E
Abstract : Objective: To assess the efficacy of prolonged high pressure angioplasty for dilatation of calcified and stenotic cardiac conduits in children. Design: A prospective study of consecutive patients presenting with calcified and stenotic conduits. Setting: Two tertiary paediatric cardiology departments. Methods: Sustained (up to five minutes), high pressure (up to 18 atmospheres), double balloon angioplasty was performed in six calcified and stenotic cardiac conduits (five consecutive patients, three male, two female, age 4 to 17 years). Four patients had right ventricle to pulmonary artery (RV-PA) conduits, and one had two venous conduits in a Fontan circulation. Results: Marked reductions in right ventricle to pulmonary artery gradients, from a median (range) of 48 (40 to 62) mm Hg to 11 (5 to 16) mm Hg, and in right ventricle to femoral artery pressure ratios, from a median of 0.8 (0.72 to 0.86) to 0.4 (0.33 to 0.44), were achieved for all RV-PA conduits. All five patients had sustained clinical improvement at follow up (median follow up 12 months) and none has required reintervention or surgery. Conclusions: Prolonged high pressure double balloon angioplasty may have a role in prolonging the interval between conduit replacements in a subset of patients with complex heart defects.